The Organization of Islamic Conference (OIC): nature, role, and the issues - Hossain, Ishtiaq (Association of Third World Studies, Inc., 2012)
This article examines the role of the Muslim majority states in the international system by looking at the features of and acheievements of the Organization of Islamic Conference (OIC). The first section of the article presents a brief description of the international society from the perspective of Islam. The second secrion analyses the nature of the OIC. The third and fourth parts the reform efforrts undertaken by the OIC, and the issues faced by the OIC respectively.